A performance model of the Trusted Cloud Computing Platform VM Launch Protocol - Kamil, Said; Thomas, Nigel (EAI Endorsed Transactions on Cloud Systems, 2016)
The adoption of the cloud computing paradigm is associated with increasing security concerns. Cloud computing service models (SaaS, PaaS and IaaS) are exposed to different security threats in each level of services. The Trusted Cloud Computing Platform (TCCP) proposes a security model that protects customers VMs at the IaaS level. In this paper, we investigate methodologies for the specification and scalability of a performance model and evaluation of the VM Launch security protocol within the TCCP model. The Markovian process algebra PEPA has been used to specify and analyse the VM Launch protocol.
Keywords: tccp security protocol; cloud computing; pepa